CULTURAL CONTINUITY AND INNOVATION: DOOR GOD IMAGERY IN MODERN VISUAL COMMUNICATION - Yutian, Ren; Dubrivna, Antonina Petrivna (Theory and practice of design, 2025)
Abstract. The purpose. The purpose of this paper is to systematically analyze the evolution of the style of regional door god paintings, revealing how folk art images enter the modern visual context through cultural translation, especially the practical transformation in the medium of book design. The study is not only committed to tracing the historical trajectory of door god images, but also emphasizes the reconstruction of their value in contemporary graphic design, in order to find a sustainable and innovative integration path for traditional visual symbols in modern design language. Methodology. Based on systematic and analytical, comparative, figurative and stylistic, complex historical, and descriptive analysis, which allowed for an in-depth study of the artistic features of door paintings in different regions of China and for drawing reasonable conclusions. The results. The research results show that as a typical representative of traditional folk art, the rich visual language of door god paintings has a high potential for transformation in modern book design. The door god paintings in the four major regions of east, west, south and north have their own characteristics: the eastern region mostly reflects the delicate and gorgeous style with soft lines; the southern region prefers bright colors and exaggerated shapes; the western door gods focus on mysterious atmosphere and religious symbols; and the northern region presents a heavy realistic, majestic and majestic style. These image languages not only provide a source of inspiration for the visual beauty of modern books, but also enhance the cultural depth and emotional resonance of books through the embedding of cultural identity and folk symbols. In the practice of modern book design, these door god images are often used to express the covers, chapter pages or local decorations of festival, folk and historical books, becoming a bridge connecting tradition and modernity, folklore and art. Scientific novelty. The scientific innovation of this study is that, from the perspective of cross-regional comparison, the artistic style of Chinese door god paintings is systematically sorted out, and its evolution model in visual design language is proposed. At the same time, the study combines the analysis of traditional folk images with modern book design practice, and constructs the logical chain of “traditional images-design language-cultural transformation” from the two levels of image culture and design application, providing a new perspective and theoretical support for the regeneration of traditional cultural symbols in the design context. In addition, the study also proposed the strategic method of “visual appropriation and redesign”, that is by retaining the core spirit of traditional images and reshaping them in modern design language in form, the contemporary expression of traditional images can be achieved. Practical relevance. This study not only provides image resources and design ideas for reference for the current book design that increasingly values cultural values, but also provides clear theoretical guidance for designers on how to understand, select and use traditional elements in practice. Especially in publications that emphasize cultural identity and regionality, the regional style classification and application model constructed by the research can effectively improve the cultural accuracy and visual appeal of the design. The study also proposed specific paths for the integration of traditional culture and modern aesthetics, including methods such as element extraction, semantic reconstruction, and media translation, which will help design works convey traditional spirit while having the appeal of modern aesthetics.